Balanced RF Rectifier for Energy Recovery With Minimized Input Impedance Variation - Muh-Dey Wei, Ya-Ting Chang, Defu Wang, Chao-Hsiung Tseng, Renato Negra (IEEE Transactions on Microwave Theory and Techniques, 2017)
A balanced RF rectifier is proposed to replace terminations in microwave circuits and thus to recycle the otherwise dissipated power in resistances. In order not to degrade the performance of the original circuits, a balanced configuration is adopted because it minimizes the variation of input impedance of the rectification circuitry. This approach achieves good input reflection coefficient over a large dynamic range and operating frequencies. The highly efficient energy recycler is composed of a 3 dB quadrature coupler and two identical RF rectifiers. The impact of amplitude and phase imbalances of the transfer characteristics of the coupler is discussed. Furthermore, an arbitrary-port-resistance coupler is studied to replace non-50- Ω terminations. The experimental verification demonstrates that the proposed circuit provides an input reflection coefficient of better than −15 dB from 2.2 to 2.5GHz over different input power levels. The measured peak RF-to-dc efficiency is 74.9% at 2.34 GHz with S11=−24dB . The proposed balanced rectifier thus significantly improves S11 over existing rectifiers and is therefore suitable for replacing resistive terminations in a large variety of circuits.